Life-Threatening Spontaneous Hematoma in Unusual Sites in Patients with COVID-19 on Anticoagulant Therapy: A Case Series - Samad, M A; Disha, Afsana Rabeya; Saha, Shovon; Amin, Rohul; Khalid, K M Saidullah (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Thromboembolic manifestations are a common phenomenon in patients affected by corona virus (SARS CoV-2). Recent studies have shown that patients with acute renal failure are also at a greater risk of venous and arterial thromboembolism, 15-30% in ICU, and 7% inpatient care. However, frequently unjudicial use of anticoagulants may develop severe life-threatening hematoma. In our hospital settings we had a dedicated COVID Unit with a Hemodialysis facility. Our Nephrology department had managed 381 patients being COVID positive along with renal impairment from March 2020 to January 2022. Among these patients, four patients developed spontaneous non traumatic hematoma in unusual sites. On admission all the patients received treatment according to our national guidelines for COVID-19. Cases: It is a retrospective analysis in a single-centered hospital. Four cases with confirmed COVID-19 with acute kidney injury and on anticoagulant therapy had developed sudden concealed bleeding. These patients had no previous history of anticoagulant therapy before admission. Case 1 developed hemorrhage in Right lower anterior paramedian deep parietal wall of abdomen, Case 2 had hematoma in retroperitoneal space and in lower third of Iliopsoas, Case 3 developed hemorrhage in left cerebral hemisphere, Case 4 had Intramuscular Hematoma in left rectus abdominis. Out of these four patients two of them required Hemodialysis and one of them went into shock. All patients included were male. The mean age was 57±19.64years. All the four patients were initially managed conservatively with keen monitoring and with proper volume resuscitation, blood transfusion and discontinuation of the anticoagulants. Three of the patients survived with conservative management and one patient died due to sudden massive cardiac arrest. The use of therapeutic anticoagulant can increase the risk of bleeding in atypical sites and may exhibit higher patient death with COVID-19 if not identified at early stage. So a risk-benefit ratio of usage of anticoagulants should be kept in mind and further clinical trials needed to justify its random use in COVID-19. J Bangladesh Coll Phys Surg 2024; 42: 393-400